Numerical analysis of effect of phase change thermal storage layer and annular fins on thermal performance of linear concentrating solar evacuated tubular collector. Issue 1 (December 2020) - Wang, Hua; Jiang, Yongjie; Zhang, Xinmin; Pang, Shusheng; Mei, Yanyang
Abstract: The effects of Phase Change Thermal Storage Layer (PCTSL) and annular fins on the thermal performance of linear concentrating solar evacuated tubular collector are numerically studied. July 15 and January 15 with relatively longer and shorter solar radiation durations are selected as the dates to simulate. Three types of linear concentrating solar evacuated tubular collectors with length of 400 mm are established, which are the traditional collector, the collector with PCTSL but without annular fins, and with PCTSL and annular fins. The results show that the maximum outlet transformer oil temperature of with PCTSL but without annular fins is 5.9 °C-10.7 °C lower than the traditional one, but the outlet oil temperature change rate of the collector with PCTSL is slow; the maximum temperature duration time of the collector with PCTSL but without annular fins is 2-2.5 hours longer than that of the traditional conditions; adding fins in PCTSL makes the outlet oil temperature reach the peak more than 30 minutes earlier. The PCTSL and annular fins studied in this paper have greatly improved the thermal performance of solar collectors and have broad application prospects.